Coagulation Factor Levels and Underlying Thrombin Generation Patterns in Adult Extracorporeal Membrane Oxygenation Patients. (September 2019) - Mazzeffi, Michael; Strauss, Erik; Meyer, Michael; Hasan, Shaheer; Judd, Miranda; Abuelkasem, Ezeldeen; Chow, Jonathan; Nandwani, Veena; McCarthy, Paul; Tanaka, Kenichi
Abstract : BACKGROUND: There is a paucity of data on the underlying procoagulant–anticoagulant balance during extracorporeal membrane oxygenation (ECMO). We hypothesized that adult ECMO patients would have an imbalance between procoagulant and anticoagulant factors, leading to an abnormal underlying thrombin generation (TG) pattern. METHODS: Twenty adult venoarterial (VA) ECMO patients had procoagulant and anticoagulant factor levels measured temporally on ECMO day 1 or 2, day 3, and day 5. In heparin-neutralized plasma, underlying TG patterns, and sensitivity to activated protein C were assessed using calibrated automated thrombogram. TG parameters including lag time, peak TG, and endogenous thrombin potential (ETP) were compared against 5 normal plasma controls (3 males and 2 females) obtained from a commercial supplier. Thrombomodulin (TM) was added to some samples to evaluate for activated protein C resistance. RESULTS: Procoagulant factors (factor [F] II, FV, and FX) were mostly in normal reference ranges and gradually increased during the first 5 ECMO days ( P = .022, <.001, <.001). FVIII levels were elevated at all time points and did not change ( P = .766). In contrast, FXI was in the low-normal range but did not increase during ECMO ( P = .093). Antithrombin (AT) and protein C levels were below normal but increased during the first 5 ECMO days ( P = .002 and P = .014). Heparinase-treated samples showed prolonged lag time, increased peak TG, and increased ETP compared to controls; mean difference in lag time on ECMO day 1 or 2 = 6.0 minutes (99% confidence interval [CI], 2.8–9.2), peak TG = 193.4 (99% CI, 122.5–264.3), and ETP = 1170.4 (99% CI, 723.2–1617.6). After in vitro TM treatment, differences in TG parameters were accentuated and ECMO samples appeared insensitive to TM treatment; mean difference in lag time on ECMO day 1 or 2 = 9.3 minutes (99% CI, 6.2–12.4), peak TG = 233.0 (99% CI, 140.9–325.1), and ETP = 1322.5 (99% CI, 764.8–1880.2). Similar differences in TG parameters were observed on ECMO days 3 and 5. CONCLUSIONS: Contact activation occurs during ECMO, but procoagulant factor levels are generally preserved. Although heparin-neutralized TG is delayed, peak TG and ETP are supranormal in the setting of high FVIII and low AT and protein C levels. Resistance to TM is also apparent. These changes demonstrate a possible mechanism for hypercoagulability during adult VA ECMO.